Wind energy diffusion in developing countries - Zwarteveen, Jan Willem (Cranfield University, 2022)
Wind energy is valuable, but many developing and emerging economies (DEEs) do not utilize their substantial wind potential. The objective of this research is to understand wind energy diffusion with the aim to promote wind energy in underdeveloped areas for sustainable benefits of both country and wind industry. The literature review and meta-analysis identified 259 factors that influenced wind energy diffusion. A novel conceptual framework that describes wind energy diffusion was developed, dissecting factors that influence wind diffusion into factors related to the desire for wind energy, factors related to the mechanism of change and disturbing factors. Regarding DEEs, the meta-analysis showed indications of the importance of economic factors and, opposing expectations, environmental factors appear not to drive wind energy growth. Based on path creation theories but using binary logistic regression as a novel quantitative approach, the empirical study explored the factors influencing early wind energy diffusion. Key indicated drivers appeared to be climate adaptation, vested interests (fossil fuels and hydropower), and the business case potential. Regarding DEEs, a negative business case potential formed a key barrier. Novel market entry strategies for the wind power Original Equipment Manufacturer (OEM) are to collaborate with vested power producers rather than compete and promote wind for climate adaptation instead of climate change mitigation. Most high wind potential countries have installed less than 500 MW of wind power capacity (commercialization threshold). The remaining countries have on average 20596 MW of wind capacity installed per country. The lagging wind adopting countries were assessed on their probability to adopt commercial wind in the near future, by using a novel quantitative path creation forecasting method. Passive entry, passive waiting, active entry and active waiting were defined as suggested market entry and development strategies for the wind OEM.
Zawwar, Imran - Associate Supervisor
Keywords: Wind Power; Diffusion; Developing and Emerging Economies; Sustainable Development Goals; Market Entry; Original Equipment Manufacturer